Effects of Aluminum chloride on some hormones levele and reproductive organs of male rats (Rattus norvegicus) - Nuhair , Rasha (University of Thi-Qar Journal of Science, 2015)
This study was conducted at the Veterinary Medicine, University of Basrah to investigate the effect of AluminiumChloride on some hormones and histological changes in the laboratory Male Rats (Rattus norvegicus). Rats sexuallymature (16 weeks age) and 250±50 gm weighing, were used, they were divided into Four groups, each one consisted of 8 male rats in , Three groups were dosed Orally with 25, 50 and 100 mg/kg B.W. aluminium in the form of HgCl for 21 days consecutive . An equivalent volume of distal water was administered to the fourth group which was set as the control group. Levels of the LH, FSH and Testosterone hormones were evaluated . in addition to histo – pathological changes of the Epididymis and testis. Results of this study indecate a significant decrease (P≤0.05) of FSH, LH and Testosterone hormones concentrations in treated groups compared with control groupe. The histopathological changes in Testis and epididymis were obvious in all treated groups comparison with control.